Compositional analysis of dietary patterns. (September 2019) - Solans, M; Coenders, G; Marcos-Gragera, R; Castelló, A; Gràcia-Lavedan, E; Benavente, Y; Moreno, V; Pérez-Gómez, B; Amiano, P; Fernández-Villa, T; Guevara, M; Gómez-Acebo, I; et al.
Instead of looking at individual nutrients or foods, dietary pattern analysis has emerged as a promising approach to examine the relationship between diet and health outcomes. Despite dietary patterns being compositional (i.e. usually a higher intake of some foods implies that less of other foods are being consumed), compositional data analysis has not yet been applied in this setting. We describe three compositional data analysis approaches (compositional principal component analysis, balances and principal balances) that enable the extraction of dietary patterns by using control subjects from the Spanish multicase-control (MCC-Spain) study. In particular, principal balances overcome the limitations of purely data-driven or investigator-driven methods and present dietary patterns as trade-offs between eating more of some foods and less of others.